Clinical Potential of Quantum Dots. (20th February 2008) - Iga, Arthur M.; Robertson, John H. P.; Winslet, Marc C.; Seifalian, Alexander M.
Abstract : Advances in nanotechnology have led to the development of novel fluorescent probes called quantum dots. Quantum dots have revolutionalized the processes of tagging molecules within research settings and are improving sentinel lymph node mapping and identification in vivo studies. As the unique physical and chemical properties of these fluorescent probes are being unraveled, new potential methods of early cancer detection, rapid spread and therapeutic management, that is, photodynamic therapy are being explored. Encouraging results of optical and real time identification of sentinel lymph nodes and lymph flow using quantum dots in vivo models are emerging. Quantum dots have also superseded many of the limitations of organic fluorophores and are a promising alternative as a research tool. In this review, we examine the promising clinical potential of quantum dots, their hindrances for clinical use and the current progress in abrogating their inherent toxicity.